Process Evaluation to Document Crucial Moments in Development of the National Neurological Conditions Surveillance System at the U.S. Centers for Disease Control and Prevention - MacDonald, Goldie; Mercer, Shawna L; Fisher, Angela H; Grigorescu, Violanda; Mac Kenzie, William R; Anderson, Mindelyn (Journal of MultiDisciplinary Evaluation, 2020)
Background: Neurological conditions or disorders strike roughly 50 million Americans annually but accurate and comprehensive national estimates for many of these conditions are not available. In 2019, Congress provided $5 million to Centers for Disease Control and Prevention (CDC) to establish the National Neurological Conditions Surveillance System (NNCSS). CDC focused initial activities on multiple sclerosis and Parkinson’s disease. Purpose: We conducted a process evaluation to document and understand multifaceted work to implement a new surveillance activity for two neurological conditions. Setting: We conducted this evaluation with government personnel internal to the Center for Surveillance, Epidemiology, and Laboratory Services at the Centers for Disease Control and Prevention in Atlanta, GA. Intervention: A new public health surveillance activity for two neurological conditions, multiple sclerosis and Parkinson’s disease, that uses existing data resources and systems. Research design: The evaluation included interviews with CDC personnel and review of administrative and programmatic information. Data were analyzed and interpreted to identify crucial moments in the first year of funded work on NNCSS. The study revealed that this surveillance activity required diverse contributions and collaboration within the federal government and with non-governmental organizations. The findings can be used to guide work to enhance surveillance for many neurological conditions. Findings: The study revealed that this surveillance activity required diverse contributions and collaboration within the federal government and with non-governmental organizations. While collaboration is a cornerstone of public health practice, it is not always well-documented in planning or implementation of surveillance or other data-related activities.